Protective effect of ginsenoside against acute renal failure via reduction of renal oxidative stress and enhanced expression of ChAT in the proximal convoluted tubule and ERK1/2 in the paraventricular nuclei - Zhou, J; Zhang, H. A; Lin, Y; Liu, H. M; Cui, Y. M; Xu, Y; Zhao, N; Ma, J. M; Fan, K; Jiang, C. L (Physiological research, 2014)
Generation of reactive oxygen species significantly contributes to the pathogenesis of acute renal failure (ARF) induced by myoglobin release. Ginsenosides (GS), the principal active ingredients of ginseng, is considered as an extremely good antioxidative composition of Chinese traditional and herbal drugs. The purpose of the present study was to investigate the protective effect of ginsenoside in rats with ARF on the changes of cholinergic nervous system in the kidney as well as on the involvement of mitogen-activated protein kinases (MAPK) in the hypothalamic paraventricular nuclei (PVN). In our assay, glycerol-induced acute renal failure in rats was employed to study the protective effects of ginsenoside. Our results indicated that the treatment of ARF rats with ginsenosides for 48 h significantly reduced lipid peroxidation, restored the superoxide dismutase (SOD) level. Meanwhile, the obvious increase of choline acetyltransferase-immunoreactivity (ChAT-IR) in the proximal convoluted tubular cells (PCT) was observed by immunohistochemistry in ARF+GS group. The same effect was also observed in the changes of p-ERK1/2-IR in the hypothalamic paraventricular nuclei. Our results suggest that ginsenoside administered orally may have a strong renal protective effect against glycerol-induced ARF, reduce the renal oxidative stress, and ginsenoside can also activate the cholinergic system in PCT, simultaneously MAPK signal pathway in the PVN was also activated.
Keywords: Ginsenosides; Up-Regulation; Paraventricular Hypothalamic Nucleus; Signal Transduction; superoxiddismutasa; potkani Sprague-Dawley; modely nemocí na zvířatech; Superoxide Dismutase; antioxidancia; Mitogen-Activated Protein Kinase 1; Rats, Sprague-Dawley; zvířata; fosforylace; Administration, Oral; Antioxidants; Disease Models, Animal; oxidační stres; signální transdukce; Glycerol; Time Factors; Lipid Peroxidation; proximální tubuly ledvin; mužské pohlaví; cholin-O-acetyltransferasa; ginsenosidy; akutní poškození ledvin; Mitogen-Activated Protein Kinase 3; Kidney Tubules, Proximal; Cytoprotection; mitogenem aktivovaná proteinkinasa 1; Malondialdehyde; Oxidative Stress; Phosphorylation; časové faktory; aplikace orální; upregulace; Choline O-Acetyltransferase; peroxidace lipidů; nucleus paraventricularis hypothalami; Animals; cytoprotekce; glycerol; malondialdehyd; mitogenem aktivovaná proteinkinasa 3; Acute Kidney Injury; Male